2002
DOI: 10.1097/00004728-200207000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helical CT in Detecting Right Ventricular Dysfunction Secondary to Acute Pulmonary Embolism

Abstract: CT may be useful in detecting RVD in patients with acute PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 17 publications
2
73
1
7
Order By: Relevance
“…However, this aspect has been investigated in prior work [15][16][17][18][19][20][21][22][23][24][25][26], and our cohort would be too small to meaningfully contribute to existing data. In this study, we solely aimed at analyzing the observer dependence of establishing the CT signs of RV dysfunction that have hitherto been described in the literature to identify the most robust and reproducible method.…”
Section: Limitationsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, this aspect has been investigated in prior work [15][16][17][18][19][20][21][22][23][24][25][26], and our cohort would be too small to meaningfully contribute to existing data. In this study, we solely aimed at analyzing the observer dependence of establishing the CT signs of RV dysfunction that have hitherto been described in the literature to identify the most robust and reproducible method.…”
Section: Limitationsmentioning
confidence: 98%
“…Contractor et al [18] and Lim et al [38] found a RVD/LVD ratio of greater than 1 measured on axial sections indicative of RV strain at pulmonary CTA, whereas others have proposed a threshold of greater than 1.5 [17,20,26]. However, the axial CT acquisition plane differs from the standard imaging planes of other cardiac imaging techniques, such as echocardiography [18][19][20][21][22]. Ventricular measurements on four-chamber views reconstructed from routine pulmonary CTA imaging data were shown to be superior to those from axial views for predicting adverse events.…”
Section: Ct In Acute Pulmonary Embolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of CT chest for detecting right ventricle dysfunction was 78% and specificity 100%, with a positive predictive value of 100%. 50 Although, this was a retrospective study of 25 patients, chest CT may provide an option for evaluating right ventricle dysfunction in COPD patients especially when ECHO Doppler proves inadequate.…”
Section: Chest Computed Tomographymentioning
confidence: 97%